Therapeutic vaccines for chronic diseases: successes and technical challenges. - Bachmann, M; Jennings, G (2011)
Chronic, non-communicable diseases are the major cause of death and disability worldwide and have replaced infectious diseases as the major burden of society in large parts of the world. Despite the complexity of chronic diseases, relatively few predisposing risk factors have been identified by the World Health Organization. Those include smoking, alcohol abuse, obesity, high cholesterol and high blood pressure as the cause of many of these chronic conditions. Here, we discuss several examples of vaccines that target these risk factors with the aim of preventing the associated diseases and some of the challenges they face.